Indonesia Penambahan Puree Kentang (Solanum tuberosum) dan Puree Labu Kuning (Cucurbita moschata) Terhadap Karakteristik Fisikokimia & Sensoris Kue Lumpur Tepung Kentang: Indonesia - Timotius O. Siwu; Erny J.N. Nurali; Riel J. J. Umboh; Lana E. Lalujan; Jolanda C. E. Lamaega; Yoakhim Y.E. Oessoe (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2026)
Kue lumpur is a traditional Indonesian cake that does not require gluten for volume development, making potato flour a potential non-gluten substitute for wheat flour. This study aimed to evaluate the physicochemical and sensory characteristics of potato flour-based kue lumpur enriched with potato puree and squash puree, while also utilizing downgraded potatoes from Modoinding, South Minahasa, as a value-added local raw material. A Completely Randomized Design (CRD) was applied with five treatments of potato puree to squash puree ratios (70:30 to 30:70) and three replications. The parameters analyzed included moisture content, texture, color (L*, a*, b*), and sensory acceptability. The results showed that moisture content ranged from 42.53% to 45.72%, texture from 9.35 to 11.70 N, and color values of L* 48.56–54.20, a* 0.80–3.33, and b* 28.93–38.96. Increasing the proportion of squash puree tended to increase moisture content and yellowness, while higher potato puree levels contributed to firmer texture. Sensory evaluation indicated that panelists’ acceptance ranged from neutral to like for color, aroma, taste, and texture. These findings suggest that the combination of potato and squash puree can produce acceptable non-gluten kue lumpur with favorable physicochemical and sensory properties based on local ingredients.